Does Co-Morbid Obsessive–Compulsive Disorder Modify the Abnormal Language Processing in Schizophrenia Patients? An fMRI Study - Bleich-Cohen, Maya; Poyurovsky, Michael; Hendler, Talma; Weizman, Ronit; Sharon, Haggai (Frontiers in Human Neuroscience, 2014)
Background: Impaired language processing is one of the most replicated findings in functional brain studies of schizophrenia (SCH). This is demonstrated by reduced activations in left prefrontal language areas (i.e., BA44/45, the inferior frontal gyrus, IFG) presented as decreased language lateralization. This finding was documented both in chronic as well as in first-episode SCH patients, arguing for a neurobiological marker for SCH. In a previous study, we demonstrated the specificity of this finding to SCH patients when compared to obsessive–compulsive disorder (OCD) patients in whom language processing was similar to healthy controls. Since a sizable proportion of SCH patients also meet DSM-IV criteria for OCD, we further sought to elucidate whether OCD attenuates abnormal prefrontal language lateralization in this unique group of schizo-obsessive patients compared to their non-OCD-SCH counterparts. Methods: We used functional magnetic resonance imaging (fMRI) to investigate regional activation and language lateralization in the left and right IFG and inter-hemispheric functional connectivity (FC) during a language task of auditory verb generation in 14 SCH patients with OCD, compared to 17 SCH patients without OCD, 13 OCD patients and 14 healthy controls. Results: No between-group differences were found in the behavioral measurements of word generation. However, while OCD patients were indistinguishable from healthy volunteers, a similarly reduced lateralization in the IFG and diminished inter-hemispheric FC was noted in the two SCH groups with and without OCD. Conclusion: The co-occurrence of OCD in SCH does not attenuate abnormal processing of language as reflected by regional IFG activity and FC. These results further support the notion that these language processing abnormalities are characteristic of SCH and that SCH–OCD combined psychopathology is more akin to SCH than to OCD.